Drug utilization pattern of antiepileptic agents among pediatric epilepsy at tertiary care teaching hospital of Gujarat: a cross sectional study - Dave, Hirenkumar H.; Trivedi, Niyati A. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Epilepsy is one of the most common neurological disorders characterized by recurrent episodic paroxysmal involuntary clinical events associated with abnormal electrical activity from the neurons. Without the knowledge of how drugs are being prescribed and used, it is difficult to initiate discussion on rationale drug use and to suggest measures to change prescribing habits for the better management. Present study was performed with an aim to study the utilization pattern of anti-epileptic drugs (AEDs) for the paediatric patients suffering from various forms of epileptic seizures. Methods: The present cross-sectional study was conducted at the epilepsy clinic of Department of Paediatrics, Tertiary Care Teaching Hospital of Gujarat, on patients diagnosed to have epilepsy July 2014 to October 2014. Hundred Paediatric patients of either gender diagnosed to had epilepsy and taking treatment from pediatric epilepsy clinic OPD, S.S.G. Hospital, and Baroda. Patient’s detailed medical history, demographic details and other required information was recorded on a prestructured data entry form. Results: Out of 100. GTCS was found to be the most common (55%) form of epilepsy among pediatric patients and Carbamazepine was the most commonly prescribed (41%) AED followed by sodium valproate (38%). 71% patients were prescribed monotherapy. Carbamazepine +Clobazam was the most commonly (7%) used combination. Conclusions: Use of appropriate AEDs in the majority of patients as per WHO guidelines, has decreased number of ADRs in this study.